The region of the envelope gene of human immunodeficiency virus type 1 responsible for determination of cell tropism. - Cann, A J (J Virol, 1992)
Different isolates of human immunodeficiency virus type 1 (HIV-1) vary in the cell tropisms they display, i.e., the range of cell types in which they are able to establish a productive infection. Here, we report on the phenotypes of recombinants between two molecularly cloned strains of HIV-1. Our results prove that the envelope glycoprotein gp120 is solely responsible for the difference in cell tropism between the two parental isolates and that no other genes or sequences are involved in determining the cell tropism of these strains. The region of the envelope involved in the determination of cell tropism includes sequences which encode the V3 loop of gp120. Control of cell tropism by this region of the virus env gene is a general phenomenon which applies to many different HIV-1 isolates.